Energy modeling as a tool for energy development - Analysis of the Macedonian energy system - Lazova, Elena; SHesho, Igor (Здружение на енергетичарите на Македонија, 2022)
In order to achieve a carbon-neutral and sustainable future, energy system modelling is one of the key tools for obtaining relevant indicators, based on which conclusions and recommendations are made. Energy modelling is developed over the second half of the twentieth century and yet there are a lot of challenges when implementing an effective energy transition plan. In this paper the software package EnergyPlan is applied for energy system modelling and the input parameters are used from the Macedonian energy system. In the model for the Macedonian energy system, several scenarios are analyzed in order to assess the potential for integration of renewable energy sources. As an evaluation parameter, the indicator Levelized Cost of Electricity was used.
Keywords: energy modeling, energetics